Manajemen Pengembangan Kurikulum di Sekolah Dasar Islam - Nurlaela, Latifah; Ulfah, Maria; Farisi, Mohammad Imam (J-MPI (Jurnal Manajemen Pendidikan Islam), 2023)
School curriculum development management is a process that involves planning, organizing, implementing, and supervising a curriculum that meets the needs and objectives of education. The purpose of this study is to describe and analyze the curriculum development management in SDIP Masyithoh and SDIT Quantum Mulia. Data collection was conducted through interviews, observations, and document analysis. The data collected were analyzed thematically. To improve the validity of the data, the researcher used triangulation. The researcher ensured that this study complies with the applicable research ethics. SDIP Masyithoh and SDIT Quantum Mulia are two Islamic schools that have different approaches to curriculum development management. SDIP Masyithoh emphasizes on strengthening Islamic values and the development of academic skills, while SDIT Quantum Mulia emphasizes on the application of technology in learning, integration of subjects, and the development of students' global competencies. These different approaches are reflected in every stage of curriculum development management, starting from planning, organizing, implementing, supervising, and evaluating. SDIP Masyithoh approach emphasizes on strengthening Islamic values and the development of academic skills, which can help students become intelligent, faithful, and virtuous individuals. Meanwhile, SDIT Quantum Mulia approach emphasizes on the application of technology in learning, integration of subjects, and the development of students' global competencies, which can help students become intelligent, creative, and leadership-minded individuals.